Urdesa: A cartography of the neighborhood. - Rodríguez, Cuqui (Artes: Architecture, Technology and Sustainability, 2025)
This paper summarizes a cartographic investigation of the Urdesa neighborhood, taking as reference the photographic archive created by the artist Daniel Adum Gilbert in 2011 and published in 2014 in the book «Urdesa» that was later contrasted with an authorial production of a photographic survey taken in 2022 of the same buildings. This exploration aims to highlight the changes that the neighborhood has undergone over the past 10 years and the way of life of its inhabitants through modifications in its architecture and, consequently, in its public space.
Keywords: cartography, archive, Urdesa, disappearances, neighborhood landscape